Regulation of the Transposase of Tn4652 by the Transposon-Encoded Protein TnpC - Hõrak, Rita (American Society for Microbiology, 1999)
Transposition is a DNA reorganization reaction potentially deleterious for the host. The frequency of transposition is limited by the amount of transposase. Therefore, strict regulation of a transposase is required to keep control over the destructive multiplication of the mobile element. We have shown previously that the expression of the transposase (tnpA) of the Pseudomonas putida PaW85 transposon Tn4652 is positively affected by integration host factor. Here, we present evidence that the amount of the transposase of Tn4652 in P. putida cells is controlled by the transposon-encoded protein (TnpC). Sequence analysis of the 120-amino-acid-long TnpC, coded just downstream of the tnpA gene, showed that it has remarkable similarity to the putative polypeptide encoded by the mercury resistance transposon Tn5041. As determined by quantitative Western blot analysis, the abundance of TnpA was reduced up to 10-fold in the intact tnpC background. In vivo experiments using transcriptional and translational fusions of the tnpA gene and the reporter gene gusA indicated that TnpC operates in the regulation of the transposase of Tn4652 at the post-transcriptional level.